Cross-species Harmony: Horses and Humans Co-Creating and Immersed in Shared Worlds - Sarah Allen (European Journal of American Studies)
Despite efforts to democratize horse/human relations, conceptions of harmony between horses and humans continue to privilege the human’s will, even in more progressive models of horsemanship. Using the tenets of Object-Oriented Ontology, this paper explores the ways in which nonhuman animal autonomy might condition cross-species connections and make harmony possible. While Object-Oriented Ontology acknowledges that all things withdraw from all things, this paper shows how touch is an access mode that can allude to and create out of the withdrawnness of the beings engaged in negotiation. In these processes of allusion and creation, we humans might simultaneously co-create and be immersed in harmonious, multispecies worlds.